The Dialectic of the Real Erotic and of Eroticism in Kierkegaard’s Seducer’s Diary - de Lacoste, Guillermine (KIERKEGAARDIANA, 2002)
The Dialectic of the Real Erotic and of Eroticism in Kierkegaard’s Seducer’s Diary